Leadership and Innovation - How Can Leaders Create Innovation-Promoting Environments in Their Organisations? (European Journal of Marketing and Economics, 2021)
Innovation is considered to be among the most relevant success factors for companies in the contemporary business environment. Thus, finding strategies and approaches to foster innovation becomes a crucial challenge for managers and leaders alike. The present paper aims to showcase, how the working environment shaped by the present Covid-19 crisis with its enforced work-from-home-setting influences innovation processes. Therefore, an extensive literature review is conducted, where in a first step the challenges of leadership within a telework-environment are established. The author therein explains the differences between classic approaches towards this mode of virtual collaboration and the pandemic-induced, often mandatory approach to telework utilized throughout the pandemic. This leads to a description of how – especially in times of the Covid-19 pandemic – innovation becomes even more crucial for organizations not only in the medical field, as they need to react to a changing environment and, accordingly, changing customer needs. Leadership challenges of finding ways to create and shape innovation-friendly work environments and organizational cultures given the limitations of the situation, are presented and critically discussed.
Keywords: Leadership, Organizational Culture, Openness and Creativity, Promoting Innovation